Hubungan Pola Konsumsi Makanan Cepat Saji dengan Risiko Obesitas pada Mahasiswa di Kecamatan Rappocini, Kota Makassar - Ilham Zaydan Fadhlurrahman; Rafli Dzuhair Alfarabi (Journal of Applied Health Sciences, 2026)
Obesity among university students has become an increasing public health concern due to changes in lifestyle and dietary patterns. Fast food, which is high in calories, fat, and sugar, is considered a major risk factor contributing to excessive weight gain. This study aims to analyze the relationship between fast food consumption patterns and the risk of obesity among students in Rappocini District, Makassar City. This research employed a quantitative design with a cross-sectional approach. A total of 150 students were selected using purposive sampling. Data were collected through structured questionnaires and anthropometric measurements to determine Body Mass Index (BMI). Data analysis was conducted using chi-square tests and logistic regression. The results showed that the majority of respondents had a high frequency of fast food consumption. Nutritional status distribution indicated that 48% of respondents were categorized as overweight and obese. Bivariate analysis revealed a significant relationship between fast food consumption patterns and obesity risk (p < 0.05). Multivariate analysis confirmed that fast food consumption is an independent risk factor for obesity, with more than twice the likelihood compared to those with lower consumption levels. In conclusion, fast food consumption patterns are significantly associated with obesity risk among university students. Preventive efforts should focus on improving dietary behavior through nutrition education, increasing access to healthy food options, and promoting physical activity within the campus environment.